Human umbilical cord mesenchymal stem cell-derived exosomes promote neurological function recovery in rat after traumatic brain injury by inhibiting the activation of microglia and astrocyte - Cui, Lianxu; Luo, Wei; Jiang, Wenkang; Li, Haomin; Xu, Junrong; Liu, Xiaocui; Wang, Bingyun; Wang, Jinhui; Chen, Guoqiang (Regenerative therapy, 2022)
Traumatic brain injury (TBI) is a serious neurological disorder with increasing worldwide incidence. Emerging evidence has shown a significant therapeutic role of mesenchymal stem cells (MSCs) derived exosomes on traumatic brain injury with broad application prospects as a cell-free therapy. However, a comprehensive understanding of its underlying mechanism remained elusive. In this study, umbilical cord mesenchymal stem cells (UCMSCs)-derived exosomes (UC-MSCs-Exo) were isolated by ultracentrifugation and injected intraventricularly in a rat model of TBI. Our results showed that UC-MSCs-Exo promoted functional recovery and reduced neuronal apoptosis in TBI rats. Moreover, UC-MSCs-Exo inhibited the activation of microglia and astrocytes during brain injury, thereby promoting functional recovery. However, the effect of UC-MSCs-Exo on the content of plasma inflammatory factors in rats was not significant. Collectively our study suggested that UC-MSCs-Exo promotes the recovery of neurological function in TBI rats by inhibiting the activation of microglia and astrocytes, providing a theoretical basis for new therapeutic strategies for central nervous system diseases.